Presentations and outcomes of familial hemophagocytic lymphohistiocytosis in the pediatric intensive care units (PICUs) - Fahad Alsohime; Fahad Alsohime; Mohamad-Hani Temsah; Mohamad-Hani Temsah; Mohamad-Hani Temsah; Rawan M. Alotaibi; Reham M. Alhalabi; Sarah AlEnezy; Aly Abdelrahman Yousef; Aly Abdelrahman Yousef; Abdullah Mohammed Alzaydi; Hussam Sameer Inany; et al. (Frontiers Media S.A., 2023)
ObjectivesWe aimed to describe Familial Hemophagocytic Lymphohistiocytosis (F-HLH) patients' clinical features, intensive care courses, and outcomes.MethodsMulti-center retrospective cohort study of pediatric patients diagnosed with F-HLH from 2015 to 2020 in five tertiary centers in Saudi Arabia. Patients were classified as F-HLH based on their genetic confirmation of known mutation or on their clinical criteria, which include a constellation of abnormalities, early disease onset, recurrent HLH in the absence of other causes, or a family history of HLH.ResultsFifty-eight patients (28 male, 30 female), with a mean age of 21.0 ± 33.9 months, were included. The most common principal diagnosis was hematological or immune dysfunction (39.7%), followed by cardiovascular dysfunction in 13 (22.4%) patients. Fever was the most common clinical presentation in 27.6%, followed by convulsions (13.8%) and bleeding (13.8%). There were 20 patients (34.5%) who had splenomegaly, and more than 70% of patients had hyperferritinemia >500 mg/dl, hypertriglyceridemia >150 mg/dl and hemophagocytosis in bone marrow biopsy. Compared to deceased patients 18 (31%), survivors had significantly lower PT (p = 041), bilirubin level of <34.2 mmol/L (p = 0.042), higher serum triglyceride level (p = 0.036), and lesser bleeding within the initial 6 h of admission (p = 0.004). Risk factors for mortality included requirements of higher levels of hemodynamic (61.1% vs. 17.5%, p = 0.001) and respiratory (88.9% vs. 37.5%, p < 0.001) support, and positive fungal cultures (p = 0.046).ConclusionsFamilial HLH still represents a challenge in the pediatric critical care setting. Earlier diagnosis and prompt initiation of appropriate treatment could improve F-HLH survival.